2021
DOI: 10.5337/2021.207
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risks from pesticide use: the case of commercial banana farming in northern Lao PDR

Abstract: The publications in this series cover a wide range of subjects-from computer modeling to experience with water user associations-and vary in content from directly applicable research to more basic studies, on which applied work ultimately depends. Some research reports are narrowly focused, analytical and detailed empirical studies; others are wide-ranging and synthetic overviews of generic problems.Although most of the reports are published by IWMI staff and their collaborators, we welcome contributions from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The widening use of herbicides and pesticides in the Mekong countries since the 2000s has been in tandem with the expansion of commodity crops. In Laos, this is particularly acute in relation to maize and banana, which are commonly introduced by cross‐border investors and traders who also supply chemical inputs to farmers (Cole, 2021; Shattuck, 2021; Wentworth et al, 2021). Reliable data are scarce, but legal imports of agrochemicals from Thailand, China and Vietnam to Laos significantly increased since the mid‐2000s, and are likely to be a fraction of total imports (LURAS, 2018), particularly with the ease of traders bringing chemicals across remote porous borders as the empirical section of this article details further.…”
Section: The Emergence Of ‘Responsible Agricultural Investment’mentioning
confidence: 99%
See 1 more Smart Citation
“…The widening use of herbicides and pesticides in the Mekong countries since the 2000s has been in tandem with the expansion of commodity crops. In Laos, this is particularly acute in relation to maize and banana, which are commonly introduced by cross‐border investors and traders who also supply chemical inputs to farmers (Cole, 2021; Shattuck, 2021; Wentworth et al, 2021). Reliable data are scarce, but legal imports of agrochemicals from Thailand, China and Vietnam to Laos significantly increased since the mid‐2000s, and are likely to be a fraction of total imports (LURAS, 2018), particularly with the ease of traders bringing chemicals across remote porous borders as the empirical section of this article details further.…”
Section: The Emergence Of ‘Responsible Agricultural Investment’mentioning
confidence: 99%
“…Reliable data are scarce, but legal imports of agrochemicals from Thailand, China and Vietnam to Laos significantly increased since the mid‐2000s, and are likely to be a fraction of total imports (LURAS, 2018), particularly with the ease of traders bringing chemicals across remote porous borders as the empirical section of this article details further. Among the few available studies on the range of chemicals in use, paraquat and glyphosate are frequently identified, with residues tending to be far above safety thresholds (Shattuck, 2020; Wentworth et al, 2021). Amid rising public concern about environmental and human exposure to agrochemicals in Laos, a recent policy paper noted that ‘application rates for herbicide are consistently 2‐4 times higher than recommended’ (LURAS, 2018, p. 5).…”
Section: The Emergence Of ‘Responsible Agricultural Investment’mentioning
confidence: 99%
“…In recent years, agricultural land area has increased rapidly across Laos, driven by foreign investments illustrated by a doubling in the number of foreign companies or factories from 2009 to 2015 (Wentworth et al 2021). The conversion of organic agriculture to conventional practices has been particularly evident in large-scale banana plantations (NAFRI, 2016); revealing a steady transition from subsistence agriculture to commercial production through the use of chemical fertilizers and pesticides.…”
Section: Introductionmentioning
confidence: 99%